2009
DOI: 10.1007/s11596-009-0318-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluorescence in situ hybridization and immunohistochemistry for assessment of HER-2 status in breast cancer patients

Abstract: The accurate assessment of a proto-oncogene, human epidermal growth factor receptor-2 gene (HER-2), is extremely important for the therapy and prognosis of breast cancer. Currently, immunohistochemistry (IHC) is the method widely used for the detection of HER-2 protein. Fluorescence in situ hybridization (FISH) has been suggested to be a golden standard assay for HER-2 amplification. This study examined the expression and amplification of HER-2 in paraffin-embedded sections of breast cancer tissues, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has been suggested that IHC is appropriate for initial HER‐2/neu assessment; however, patients with tumors scores interpreted as 2+, would benefit from FISH to more accurately assess Her‐2/neu status and avoid unwarranted treatment and prognostication . To assess the feasibility and accuracy of FISH for Her‐2/neu on FNA, we chose 50 cases with 3+/2+ status (by IHC on histology) for performing FISH in corresponding MGG stained slide.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that IHC is appropriate for initial HER‐2/neu assessment; however, patients with tumors scores interpreted as 2+, would benefit from FISH to more accurately assess Her‐2/neu status and avoid unwarranted treatment and prognostication . To assess the feasibility and accuracy of FISH for Her‐2/neu on FNA, we chose 50 cases with 3+/2+ status (by IHC on histology) for performing FISH in corresponding MGG stained slide.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some evidence that FISH testing predicts the therapeutically significant Her-2/neu status more accurately, the approach of primary immunohistochemistry screening with supplementary FISH molecular confirmation is widely used. Nevertheless, many centers recommend the initial assessment of cases of invasive breast cancer by IHC supplemented by FISH when IHC results are equivocal [17][18][19]. Several studies showed that score 2+ Her-2/neu by IHC is infrequently accompanied by true gene amplification [2,7,9], while others reported significant higher rates [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Such cases with score 2+ by IHC and with negative gene amplification are considered false positive by IHC. Possible explanations for these results could be attributed to variation in time fixation, processing conditions that can lead to variation in the intensity of staining especially with the use of heat inactivation epitope retrieval that can cause false positive results [18,21,22]. Tumor heterogeneity is another possible explanation which is documented in many tumors with the presence of a clone that is biologically different from nearby clones [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, it still leaves many drugs and medical consumables needed for treating critical illnesses uncovered. Moreover, this program has a single source of funds, offers limited security, and suffers from low efficiency (Wu et al, 2019). Many families have had to forego treatment due to huge medical expenses (Shen and Li, 2013).…”
Section: The Origins and Current Situation Of Medical Crowdfundingmentioning
confidence: 99%